Challenges and Factors Affecting Localization of Nursing Workforce at Saudi Arabia – A Scoping Review - Hamouda, Ghada; Felemban, Ohood; Al- Dhwan, Rahmah Ali Hassan (Journal of medical and pharmaceutical sciences, 2022)
The study aimed to identify the challenges and factors that affect the localization of the nursing workforce in Saudi Arabia. To achieve this objective, the study used the scoping review method through reviewing previous studies, where the number of studies reviewed reached (19) studies. The study reached several results, the most important of which are: there is a severe shortage of Gulf human cadres in the field of nursing, due to the low view of the profession, which prevents males and females from working in it. The mixing imposed by the necessities of the profession, and the possibility of the nurse providing services to male patients, which prompts the family not to enroll their daughters in this educational and career path. In addition, the study found that the low salary scale prevents engaging in the nursing profession. The study recommended a number of recommendations, including: educating citizens and spreading adequate awareness of the importance of the nursing profession in society, and changing the society’s view of it. In additional to that, the need to develop local nursing competencies through holding training courses and workshops to compete with foreign competencies. also, the study recommended supporting and motivating students to enroll in nursing colleges in the Kingdom, and providing all logistical services from medical supplies, devices, equipment and materials for the health care system. It also recommended providing institutional support to nursing workers and persuading the administrative leadership and its commitment towards the localization of the workforce.